Cervical dystonia: clinical and therapeutic features in 85 patients - Camargo, Carlos Henrique Ferreira; Teive, Hélio Afonso Ghizoni; Becker, Nilson; Baran, Maria Helena Herdoíza; Scola, Rosana Hermínia; Werneck, Lineu César (My University, 2008)
We studied patients with cervical dystonia (CD) to determine clinical features and response to botulinum toxin A (BoNT/A). Patients were submitted to clinical, laboratory and neuroimaging evaluation. BoNT/A was injected locally in 81 patients using electromyographic guidance. Four patients who had had previous treatment were considered to be in remission. The average ages at onset of focal dystonia and segmental dystonia were greater than for generalized dystonia (p0.0003). The severity of the abnormal head-neck movements were more severe among the patients with generalized dystonia (p0.001). Pain in the cervical area was noted in 59 patients. It was not possible to determine the etiology of the disease in 62.3% of patients. Tardive dystonia was the most common secondary etiology. A major improvement in the motor symptoms of CD and pain was observed in patients following treatment with BoNT/A. The tardive dystonia subgroup did not respond to the treatment. Dysphagia was observed in 2.35% of the patients.

Para identificar os aspectos clínicos e a resposta a toxina botulínica A (TxBA), pacientes com distonia cervical (DC) foram submetidos a avaliação clínica, laboratorial e neuroimagem. o tratamento com TxBA foi aplicado a 81 pacientes guiado por eletroneuromiografia. Quatro pacientes, com tratamento prévio, foram considerados em remissão. A média de idade de início dos sintomas de pacientes com distonia focal e segmentar foi maior que a encontrada em pacientes com distonia generalizada (p0,0003). A gravidade das alterações motoras cervicais foi maior entre os pacientes com distonia generalizada que nos pacientes com distonia focal (p0,001). Graus diferentes de dor na região cervical foram relatados por 59 dos pacientes. Não foi possível determinar a etiologia da doença em 62,3% dos pacientes sendo distonia tardia a mais comum. Houve acentuada melhora dos sintomas motores e da dor da DC com a aplicação de TxBA. o subgrupo de pacientes com distonia tardia não respondeu ao tratamento. Disfagia ocorreu em 2,35% dos pacientes.
Distonia cervical: aspectos clínicos e terapêuticos de 85 pacientes
Keywords: Dystonia; Cervical dystonia; Botulinum toxin; Dysphagia